A competitive and reversible deactivation approach to catalysis-based quantitative assays - Kazunori Koide (Nature Portfolio, 2016)
Assays for catalytic systems—particularly ones with simple colorimetric readouts—are useful for the rapid evaluation of performance. Here, the authors report an assay based on a concurrent colour-forming reaction working across a wide range that can be stopped to allow measurements and subsequently restarted.